PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK DI KELAS XI TKR SMK NEGERI 3 TABANAN SEMESTER GANJIL TAHUN PELAJARAN 2019/2020 - I Ketut G Cakra Partana (Widyadari, 2023)
In the implementation of learning needs to be done continuous improvement. One way of improvement that can be done is to use an appropriate learning model. To find out how effective the learning model used is, the teacher needs to conduct research that does not interfere with the learning process or research that adapts to the learning conditions at that time. This classroom action research was carried out at SMK Negeri 3 Tabanan in Class XI TKR in the odd semester of the 2019/2020 academic year. At the beginning of the study, an initial test was carried out with the results of the ability of students for the subject of chassis maintenance and light vehicle power transfer which was still low. The purpose of writing this class action research is to find out whether the Inquiry learning model can improve student learning achievement. The data collection method is a learning achievement test. The method of data analysis is descriptive quantitative. The results obtained from this study are that inquiry can improve student learning achievement. This is evident from the results of student achievement obtained in Cycle I an average of 73 (scale 1-100). To ensure these results, cycle II was carried out by making improvements to the weaknesses found in cycle I. The learning achievements of students from Cycle I averaged 83 (scale 1-100). By making some improvements to the application of the learning model from cycle I to cycle II, it increased by 9.9%. The conclusion obtained from this research is that the inquiry learning model can improve learning achievement.